Prospective study on antimicrobial resistance in leprosy cases diagnosed in France from 2001 to 2015. (November 2018) - Chauffour, A.; Lecorche, E.; Reibel, F.; Mougari, F.; Raskine, L.; Aubry, A.; Jarlier, V.; Cambau, E.; ,
Abstract: Antimicrobial resistance (AMR) in leprosy is mostly unknown because Mycobacterium leprae does not grow in vitro and bacteriologic investigations have been abandoned. However, molecular detection of resistance can be applied to multibacillary cases. Patients living in France mainland or in the French territories and diagnosed with leprosy from 2001 to 2015 were prospectively studied for AMR by detecting mutations in rpoB for rifampicin resistance, in folP1 for dapsone and in gyrA for ofloxacin. Single nucleotide polymorphism (SNP) genotypes 1–4 were determined for resistant strains. Of 334 skin biopsy samples received for suspicion of leprosy, 184 (55.1%) were positive for M. leprae (acid-fast bacilli and M. leprae –specific repetitive element PCR) corresponding to 160 multibacillary cases. AMR was detected in 18 cases (11.3%): 13 cases (8.1%) of dapsone resistance, three (1.9%) rifampicin and two (1.3%) ofloxacin. There were no strains with multidrug resistance. The mutations (numbering system of M. leprae TN strain genome) found were P55L (n = 7), T53I (n = 5), T53A (n = 1) in folP1 ; S456L (n = 2) and S456F (n = 1) in rpoB ; and A91V (n = 2) in gyrA . Resistance proportion differ significantly between new and relapse cases (9/127, 7.0%, vs. 9/33, 25.7%, p 0.003). The frequency distribution of SNP1–4 types of resistant strains was two, one, 12 and three with five SNP3 cases from New Caledonia harbouring the same T53I FolP1 substitution. This is the first report of AMR surveillance for new and relapse cases of leprosy in Europe. Detection of resistance helped in individual treatment as well as in epidemiologic investigations. Graphical abstract: